Internal architecture of the proximal femur: calcar femorale or Adams' arch? - Bartoníček, Jan; Alt, Jan; Naňka, Ondřej (International orthopaedics, 2023)
PURPOSE: The calcar femorale (femoral calcar) is used in the English literature to designate the thickened medial cortex of the femoral neck. This term is, however, incorrect, as the calcar femorale is actually quite another structure. METHODS: Searching was performed in original and historic publication. RESULTS: The importance of the thickened medial cortex of the proximal femur in femoral neck fractures was discussed already by Robert Adams in 1834-1836. Therefore, the German surgeon C.W. Streubel, in 1847, called it Adamscher Knochenbogen (Adams' arch). Due to misspelling, this term was gradually changed to Adambogen, and at the turn of twentieth century, it was commonly used primarily in the German literature. Then, it fell into oblivion and its "renaissance" came as late as during the 1960s, again in the German literature, in connection with operative treatment of trochanteric fractures. CONCLUSIONS: However, under the influence of the English literature, it has been replaced by the term calcar femorale (femoral calcar), used ever since. The term Adams' arch should be reserved for the thickened medial cortex of the proximal femur, while the term calcar femorale (femoral calcar) should be used for the vertical plate arising from the medial cortex close below the lesser trochanter.
Keywords: dolní končetina; femur; Femur Neck; Calcar femorale; Lower Extremity; Femur; Humans; krček femuru; Bone Plates; kostní destičky; lidé; Structure of proximal femur; Adams’ arch; Anatomy; History